Investigating outcomes of coronary artery bypass graft (CABG) surgery: a single-center retrospective study in Jordan - Emad Hijazi (Future Science OA)
Background Coronary artery bypass graft (CABG) surgery brings significant cardiac benefits but also risks post-operative complications, including cognitive impairments and infections.Materials & methods We analyzed 108 patient records between 2011 and 2021 at the Princess Muna Al-Hussein Cardiac Center, Irbid, Jordan. The primary endpoint was the occurrence of postoperative events.Results Few patients (8.3%) faced complications like stroke and infections, with age and ICU stay length as significant risk factors. Patients with complications often experienced left ventricular impairments and required inotropic support.Conclusion The study highlights the need for understanding CABG surgery complications to improve outcomes, emphasizing preventive care and personalized follow-up.